The Role And Place of Corporate Social Responsibility In The Public Relations Practice In Poland: A Qualitative Study - Dariusz TWORZYDŁO; Norbert ŻYCZYŃSKI; Sławomir GAWROŃSKI; Agata OPOLSKA – BIELANSKA; Przemysław SZUBA (Communications of International Proceedings, 2023)
The article presents the results of a study on the role and place of corporate social responsibility, understood as the organisation's responsibility for the impact of its decisions and actions on society and the environment, in the practice of public relations in Poland. In addition to the theoretical part, an important component is the results of a quantitative research, conducted among public relations professionals in September/October 2021 on a sample of 421 people. The selection of the sample was purposeful, however, it allowed us to collect information from both practitioners and researchers in the field of PR. The objective of the article is to indicate the essence and importance of conducting CSR activities in the public relations industry, as well as to identify the changes that take place in the area of CSR activities undertaken by public relations practitioners. The results also indicate that ethical values are receiving an increasing importance in decision-making processes with an increasing role and the importance of public awareness. Properly implemented public relations activities improve a company's method and quality of dialogue with the society, which becomes increasingly important in the context of satisfying both business and social needs.
Keywords: corporate social responsibility; public relations; social communication; stakeholder engagement